Evaluation of Nutrients Intake for a Group of Jordanian Older Adults with Sarcopenia Syndrome in Amman: An Explorative and Pilot Study - Sarah Ziad Al-Majali; Hadeel Ali Ghazzawi; Adam Tawfiq Amawi (Journal of Aging Research)
Aim. Sarcopenia is an age-related syndrome that is characterized by a progressive loss of muscle mass, strength, and function. This study was performed in order to evaluate nutrients intake and physical activity level and to investigate the effect of sarcopenia syndrome on food intake for a group of Jordanian older adults with sarcopenia syndrome in Amman. Methodology. The study sample consisted of 25 nonsarcopenic people and 25 sarcopenic patients aged over 60 years old with a male to female ratio of 1 : 1. A special questionnaire was used to collect demographic data, health data, data about syndrome characteristics, nutritional assessment, and physical activity level. A 24-hour recall was also used to collect food intake data. Body weight, height, and skinfold thicknesses were measured. Results. The mean of the sarcopenic patients’ age was 77.5 ± 6.9 years, and the mean of the weight was significantly lower in sarcopenic patients than the nonsarcopenic people. In this study, all macronutrients and micronutrients from dietary intake information were analyzed. Vitamin intake (water- and fat-soluble), as well as minerals (major and trace), amino acids, and essential fatty acids, was assessed. The mean intake of energy and carbohydrates, fat, and dietary fiber was lower than their recommendations, while the mean intake of protein was within the range of its recommendations in the sarcopenia group. The mean of the intake of omega 3 and omega 6 was below their recommendations. Conclusion. It could be concluded that sarcopenic older patients in Jordan have similar characteristics with patients studied worldwide with regard to age of patients, female to male ratio, and main symptoms. Sarcopenic older patients in Jordan generally have lower weight and BF% than nonsarcopenic adults and have inadequate dietary intake compared to their recommendations and compared to nonsarcopenic older adults. Therefore, the diet of sarcopenic patients needs modification and follow-up. The level of physical activity and daily living activities for sarcopenic older patients is lower than that of nonsarcopenic older adults.